Evidence of hydrogen trapping at second phase particles in zirconium alloys - Christopher Jones (Nature Portfolio, 2021)
Abstract Zirconium alloys are used in safety–critical roles in the nuclear industry and their degradation due to ingress of hydrogen in service is a concern. In this work experimental evidence, supported by density functional theory modelling, shows that the α-Zr matrix surrounding second phase particles acts as a trapping site for hydrogen, which has not been previously reported in zirconium. This is unaccounted for in current models of hydrogen behaviour in Zr alloys and as such could impact development of these models. Zircaloy-2 and Zircaloy-4 samples were corroded at 350 °C in simulated pressurised water reactor coolant before being isotopically spiked with 2H2O in a second autoclave step. The distribution of 2H, Fe and Cr was characterised using nanoscale secondary ion mass spectrometry (NanoSIMS) and high-resolution energy dispersive X-ray spectroscopy. 2H− was found to be concentrated around second phase particles in the α-Zr lattice with peak hydrogen isotope ratios of 2H/1H = 0.018–0.082. DFT modelling confirms that the hydrogen thermodynamically favours sitting in the surrounding zirconium matrix rather than within the second phase particles. Knowledge of this trapping mechanism will inform the development of current understanding of zirconium alloy degradation through-life.